2008
DOI: 10.1103/physrevb.78.012408
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical control of the magnetization direction in high aspect-ratio PdNi ferromagnetic nanoelectrodes

Abstract: Abstract:We present a study of electron-beam evaporated Pd 0.4 Ni 0.6 alloy thin films by means of ferromagnetic resonance measurements on extended films of varying thickness and anisotropic magnetoresistance measurements of lithographically patterned high aspect-ratio ferromagnetic electrodes, respectively. The results reveal that the direction of the magnetization strongly depends on the electrode lateral dimensions, transitioning from in-plane magnetization for extended films to out-of-the-plane magnetizati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…This value is of the same order of magnitude as previously obtained by FMR for infinite films. 15 The anisotropy can be linked to a difference of temperature via the following relation (valid for an infi- Fig. 7, but computed for a deformable Si substrate (treated as an isotropic medium with E = 185 GPa and ν = 0.26).…”
Section: Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This value is of the same order of magnitude as previously obtained by FMR for infinite films. 15 The anisotropy can be linked to a difference of temperature via the following relation (valid for an infi- Fig. 7, but computed for a deformable Si substrate (treated as an isotropic medium with E = 185 GPa and ν = 0.26).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Additionally, anisotropic magnetoresistance (AMR) measurements performed on electrodes (with an estimated 40 % palladium content) showed that the magnetization was very far from the longitudinal orientation. 15 From a comparison of AMR signals measured for fields oriented along several directions, that study concluded moreover that the magnetization was, on the average, tilted out of the plane. The existence of a strong perpendicular anisotropy in infinite films was also directly confirmed by ferromagnetic resonance measurements, 15 and could also be guessed from the extraordinary Hall effect measurements on 90 % Pd rich samples.…”
Section: Introductionmentioning
confidence: 98%
“…FMR measurements were carried out at room temperature with a high-frequency broadband (1-50 GHz) micro-coplanar-waveguide (l-CPW) 20 using the flip-chip method, [21][22][23] by which the sample is placed up-side-down covering the central part of the CPW (as shown in Fig. 1(b)), where the transmission line is constricted to increase the density of the microwave field and enhance sensitivity.…”
mentioning
confidence: 99%
“…The resonance field increases as the magnetic field is directed away from the film plane (i.e., increasing h), as expected for a thin film ferromagnet with in-plane shape magneto-anisotropy. The angular dependence of the FMR field (H R ) can be fitted using the resonance frequency condition given by the Smit and Beljers formula, 23,24 x…”
mentioning
confidence: 99%
“…Previous studies on the Pd/Ni bilayer reported an interesting effect: a sizable enhancement of the g-factor ͑ϳ2.3͒ with respect to a bare Ni layer ͑2.2͒ was found even for bilayer systems containing very thick Ni layers. 23 Quite naturally, the role of the NM layer in this enhancement was suspected but no quantitative evidence was offered. Furthermore, the Pd/Ni system is analogous electronically to the Co/Cu system, e.g., charge transfer.…”
mentioning
confidence: 99%